Conception, Discovery, Invention, Serendipity and Consortia: Cyanobiphenyls and Beyond - John W. Goodby; Stephen J. Cowling (Crystals, 2022)
In the 1960s, a world-wide change in electronic devices was about to occur with the invention of integrated circuits. The chip was upon us, which instantly created the need for a revolution in visual communication displays. From the watch to the computer monitor, to TVs, to the phone, nearly all everyday applications were affected. A strange connection in technology underpinned these changes; the linkage between silicon semiconductors and organic compounds that did not know if they were solids or liquids. Liquid crystals had been known since 1888 and had seen little usage until they were inserted between conducting glass slides and an applied electric field. Suddenly, the possibility of driving images with low voltage fields became obvious. Many major companies took up the challenge of commercialisation, but in the UK a curious combination of government research facilities, electronic companies and one small university came together in 1970 to form a consortium and within two years the basis for new technologies had been founded. Chemistry is part of this story, with new conceptions, discoveries and inventions, and the luck to be in the right place at the right time.